Cartographie géomorphologique appliquée au périglaciaire - Hamelin, Louis-Edmond (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1963)
The writer proposes a simple and practical set of symbols for use in the preparation of periglacial maps. These maps can he constructed rapidly and at modest cost.In a preliminary section dealing with cartographie principles, the writer proposes that jour aspects of periglacial studies he mapped ; phenomena, « conditions  », regions, and aspects of applied periglacial studies. Attention will also he given to chronology. Symbolisation conforms to the following scheme : drawings or designs for phenomena, lines and curves for conditions, line patterns for regions, and letters to indicate aspects of applied periglacial studies. Colours can he used where more than one cold period has occurred. The writer proposes in Table I (in pocket) the use of more than one hundred symbols for the representation, on a 1:50,000 base map, of periglacial phenomena. The problems of classification of periglacial phenomena are also discussed, with the writer suggesting a classification based upon group of process. Among the categories included are : gelisolation, gelifraction, gelifluction, nivalisation, action of floating ice, gelifluviation, wind action and polygonation.The text ends with a glossary of periglacial terms.